Cooking solo : the joy of cooking for yourself - Miller, Klancy (Houghton Mifflin Harcourt, 2016)
Collects one hundred simple, quick recipes designed for single-diner meals, eliminating the need for scaling down ingredients, including such options as Tahitian noodle sandwich, smoked duck breast salad, and mackerel with lemon and capers.